Vegetarian times everything vegan / [Edited by] Mary Margaret Chappell - Chappell, Mary Margaretedited
Presents a collection of 250 vegan recipes, which include soups, stews, salads, main dishes, and desserts, along with helpful hints on food shopping, the preparation of ingredients, and cooking times.